Understanding the enhancement of electrochemical properties of NiCo layered double hydroxides via functional pillared effect: An insight into dual charge storage mechanisms. (20th August 2017) - Lin, Yinyin; Xie, Xiangli; Wang, Xin; Zhang, Bing; Li, Cunjun; Wang, Hai; Wang, Linjiang
Graphical abstract: As-prepared NiCo layered double hydroxide nanosheets via the intrinsic pillar effect of sodium dodecylbenzene sulfonate (NiCo-SDBS-LDH), and found that the surface redox and intercalation behaviors take effect simultaneously in NiCo-SDBS-LDH via electrochemical analysis. Highlights: An insight into dual charge storage mechanisms was proposed for NiCo-SDBS-LDH. NiCo-SDBS-LDHs were prepared via the pillar effect of the SDBS. Functional pillar leads to improved electrochemical properties of NiCo-SDBS-LDH. Ion intercalation should be considered when designing LDH-based supercapacitors. Abstract: In terms of the charge storage mechanism of supercapacitors, there are three types, including electrical double layer (EDL), surface redox reaction and intercalation reaction. The surface redox mechanism of transition metal-layered double hydroxides (TM-LDH) supercapacitor had been previously revealed. A dual charge storage mechanism integrated with surface redox and ion intercalation for LDH-based supercapacitors, however, is seldom reported before. For this purpose, here, we synthesized NiCo layered double hydroxide nanosheets via the intrinsic pillar effect of sodium dodecylbenzene sulfonate (NiCo-SDBS-LDH), and found that the surface redox and intercalation behaviors take effect simultaneously in NiCo-SDBS-LDH via electrochemical analysis. The NiCo-SDBS-LDH electrode having a relatively low specific surface area (15.28 m 2 g −1 ) still exhibited a remarkable specific capacitance of 1094 F g −1 at a scan rate of 5 A g −1, and super long cycle life of 81% retention over 3000 cycles. A dual charge storage mechanism is subsequently proposed based on the analysis of our results to explain the excellent properties of NiCo-SDBS-LDH. We believe that the enhancements should mainly be ascribed to the structural feature of the SDBS stabilized NiCo-LDH and the expanded interlayer space of NiCo-SDBS-LDH. These findings open new doors to functional pillared effect to control the electrochemical behaviors of TM-LDH-based materials.